The influence of injury and illness on total haemoglobin mass - Gough, C. E.; Sharpe, K.; Garvican, L. A.; Anson, J.; Saunders, P. U.; Gore, C. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Inclusion of total haemoglobin mass (Hbmass) in the Athlete Blood Passport would improve its sensitivity to acute autologous blood transfusion (1), a form of blood doping that is currently undetectable. The relative stability of Hbmass in non-doping athletes compared to doping athletes makes it potentially suitable for inclusion in the ABP (2) but reports of large (13-19%) Hbmass fluctuations in some injured athletes could compromise its reliability (3,4). This study quantified the effects of reduced training, surgery and changes in body mass on Hbmass in injured or ill athletes, and examined the doseresponse effect of a decrease in training on Hbmass. Fifteen athletes (6 m, 9 f) were monitored for Hbmass a mean of 9 (± 6; SD) times over 162 (± 198) days, spanning a phase of their training involving a prolonged period of injury or illness. Additionally, body mass was recorded, as were details of recent altitude exposure, iron supplementation, blood donation or surgery. Details of the athletes` training (type, duration and intensity) were recorded and compared to pre-injury training load. Linear mixed models were fitted with ln(Hbmass) as response variable, Sex, Altitude, Surgery, Iron, Training and (log of) Body Mass as fixed effects and Athlete as a random effect. Detailed models of training intensity and volume, and combined models of training load were assessed for their effect on Hbmass. Using a simple dichotomous model of combined training load, a decrease from HIGH to LOW training led to a significant 2.3% (0.3 to 4.3, 95% confidence interval; p=0.02) decrease in Hbmass. When training variables were examined in more detail, there was no significant association for any other training model with Hbmass. Surgery was associated with a 2.7% (-5.4 to -0.1, p = 0.04) decrease in Hbmass and a 10% decrease in body mass led to a 1.3% decrease in Hbmass. Reduced training, surgery and reduced body mass are each, separately, associated with significant Hbmass decreases in injured and ill athletes. These estimates could be used to differentiate the effects of injury-induced changes in Hbmass from doping if incorporated into the ABP. It was not possible with any real certainly to estimate the dose-response effect of training reductions on Hbmass using these data